A PRELIMINARY STUDY ON THE FEEDING ECOLOGY OF SULAWESI SAILFIN LIZARD (Hydrosaurus celebensis) IN BANTIMURUNG BULUSARAUNG NATIONAL PARK - Hamzah, Andi Siady; Ngakan, Putu Oka; Achmad, Amran; Nasri, Nasri (Media Konservasi, 2023)
The sailfin lizard (Hydrosaurus celebensis) is a unique reptile species whose population may be threatened by habitat destruction as well as local and global trade. As an anticipation of extinction, sufficient ecological information is required to support its conservation efforts. On the other hand, information on its ecology is still limited. The aim of this study was to collect information on its feeding ecology. This study was conducted for 78 days from June to August 2022. Direct observations were made on sailfin lizards to determine when they started feeding and the species of plants and animals consumed. To determine the availability of forage plants, we set up 22 10 x10 m plots with 5 x 5 m subplots. The results showed that the sailfin lizard started to forage at noon. They ate more plants than animals. There were 18 plant species and 7 animal species eaten by sailfin lizards. Codiaeum variegatum, which had the largest canopy cover area, was the most prevalent species of forage plant. In general, it is also relatively abundant for animal feed. Ficus hispida and Davalia trichomanoides are the two forage plant species that are most frequently consumed out of the total of 18. One species, the river crab (Gecarcinucoidea), was the only one of the seven species of animal source that was frequently consumed. Key words: Sailfin lizard, Hydrosaurus, feeding ecology